2018
DOI: 10.1016/j.heares.2018.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Input-output curves of low and high spontaneous rate auditory nerve fibers are exponential near threshold

Abstract: Input-output (IO) properties of cochlear transduction are frequently determined by analyzing the average discharge rates of auditory nerve fibers (ANFs) in response to relatively long tonal stimulation. The ANFs in cats have spontaneous discharge rates (SRs) that are bimodally distributed, peaking at low (<0.5 spikes/s) and high (∼60 spikes/s) rates, and rate-level characteristics differ depending upon SR. In an effort to assess the instantaneous IO properties of ANFs having different SRs, static IO-curves wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 51 publications
3
17
0
Order By: Relevance
“…3C). Refractoriness therefore is not the mechanism responsible for skewing the period histograms, in contrast to what has been proposed (Horst et al, 2018), or for preventing peak clipping at high SPLs.…”
Section: Refractoriness Affects Phase Locking In a Frequency-dependenmentioning
confidence: 55%
See 3 more Smart Citations
“…3C). Refractoriness therefore is not the mechanism responsible for skewing the period histograms, in contrast to what has been proposed (Horst et al, 2018), or for preventing peak clipping at high SPLs.…”
Section: Refractoriness Affects Phase Locking In a Frequency-dependenmentioning
confidence: 55%
“…When P(t) is a sinusoid, Equation 8 yields the von Mises distribution (Ashida et al, , 2013van Hemmen, 2013) scaled to represent an instantaneous rate. Such an equation has been used previously to model period histograms from ANF responses to low-frequency tones of low and moderate stimulus levels (Siebert, 1970;Colburn, 1973;Johnson, 1974;Heinz et al, 2001;Colburn et al, 2003;Horst et al, 2018). The concentration parameter of the von Mises distribution is equal to the dimensionless product BP 1 of the slope factor B and the amplitude of the sinusoid, P 1 .…”
Section: The Exponential Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Ward et al 22 argue that SR might also be observed in the case of a "soft threshold", i.e., a non-linear transfer function between instantaneous input and output, such as an exponential or logistic function, if sufficiently steep. The phase-locked period histograms of mammalian auditory-nerve fibers to low-frequency tones can be well described by exponential transfer functions relating the instantaneous stimulus pressure to the instantaneous spike rate (e.g., 26,27 ). However, it appears from comparing the data in these studies with the findings of Ward et al 22 (their Figure 6) that at the low, near-threshold stimulus levels the transfer functions are not steep enough to allow for SR. Later, Greenwood et al 28 reported that for SR to occur it is important that the signal is located near a transition between a relatively flat and an increasing portion (an 'edge') of the transfer function, while the slope of the function, in itself, would not be of great importance.…”
Section: Discussionmentioning
confidence: 99%